2007
DOI: 10.1111/j.1365-4632.2007.03338.x
|View full text |Cite
|
Sign up to set email alerts
|

Clindamycin phosphate scavenges hydroxyl radical

Abstract: This is the first report of the direct scavenging effect of CLDMP on hydroxyl radical, and the effect may improve the inflammatory response caused by invading bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…In addition, some drugs used in acne treatment, such as tetracycline and macrolide, show the ability to suppress an inflammatory reaction mediated by ROS in addition to their antibacterial activity 3,32. Furthermore, clindamycin scavenges hydroxyl radical, whereas it does not scavenge superoxide anion radical 33. In the present study, zinc ascorbate was found to have SOD-like activity, and it is possible that this compound can suppress ROS production.…”
Section: Discussionmentioning
confidence: 46%
“…In addition, some drugs used in acne treatment, such as tetracycline and macrolide, show the ability to suppress an inflammatory reaction mediated by ROS in addition to their antibacterial activity 3,32. Furthermore, clindamycin scavenges hydroxyl radical, whereas it does not scavenge superoxide anion radical 33. In the present study, zinc ascorbate was found to have SOD-like activity, and it is possible that this compound can suppress ROS production.…”
Section: Discussionmentioning
confidence: 46%
“…This may be also due to the fact that phosphate was believed to be a hydroxyl radical scavenger [27], indicating a more negative anion effect occurred in the case of this PO 4 3− species rather than that demonstrated with Cl − . Fig.…”
Section: Effect Of Anionsmentioning
confidence: 95%
“…Similarly, other studies have quantitatively analyzed the rate of HO • generation from water exposed to ultrasonic irradiation [33–35]. …”
Section: Application Of Esr To Measure Oxygen Free Radicalsmentioning
confidence: 99%
“…In fact, we recently proposed HOOOH to be one such candidate molecule, as summarized in Fig. 7 [35]. …”
Section: Evaluation Of Oxidative Stress By Esrmentioning
confidence: 99%